The Manasik of Hajj in Indonesia: Looking for Legal Certainty through the Reasonings of Usul al-Fiqh - Nasrullah, Nasrullah (Al-Risalah, 2020)
The paper aims to seek legal certainty of the manāsik in Indonesia from the perspective of uṣūl al-fiqh. In the classical fiqh, the manāsik has not received proper attention. Hence, the legal position of manāsik has thus far no definite (qaṭʿī) answer. For today's Indonesia, although the manāsik is understood more as training for prospective pilgrims on how to perform the ḥajj correctly, yet it is different from what the Prophet Muhammad practiced, which was conducted directly within the ḥajj rituals. With that aim in mind, this paper uses the reasoning devices of uṣūl al-fiqh such as bayānī, ta‘līlī, and istiṣlāhī toward the relevant literary sources in establishing a legal certainty of the manāsik. The bayānī method shows that the texts of the prophetic traditions contain imperative expression (amr), meaning that the manāsik is an obligatory practice. The taʿlīlī points out that the manāsik stands as ʿilla for the perfection of ḥajj; the manāsik is necessary to make ḥajj ritual ideally conducted. The istiṣlāḥī method reveals that the manāsik contains the value of maṣlaḥa, which is the validity of ḥajj based on sharia principles. Finally, from the perspective of maqāṣid al-sharīʿa, the necessity of the manāsik is classified into ḍarūriyya and ḥājiya. Hence, based on these arguments, this paper argues that the manāsik of ḥajj is obligatory for prospective pilgrims.